The Performance of Authenticity: The Makings of Jazz and the Self in Autobiography - Espada-Brignoni, Teófilo (Lexington Books, 2022)
In The Performance of Authenticity: The Makings of Jazz and the Self in Autobiography Teófilo Espada-Brignoni analyzes the autobiographies of New Orleans musicians (Baby Dodds, Sidney Bechet, Pops Foster, and Lee Collins) who throughout their texts construct New Orleans jazz as an authentic musical expression grounded in their experiences and culture. The author argues the autobiographies reproduce and reinterpret modernist conceptions of authenticity to assert and affirm authority over the public representations and discussions of jazz. Through the autobiographers' use of ideas about authenticity, they establish the value of their narratives but at the same time reinforce some of the power dynamics they set out to criticize. Their narratives also reveal the complex ethics that emerged during the first decades of the music and problematize modernist values such as individualism, the dichotomy of work and life, as well as the self and the social. The book adopts Foucauldian and social-constructivist perspectives, complementing analysis of the autobiographies by drawing from literary theory, psychology, sociology, and jazz scholarship.